Astigmatism compensation in digital holographic microscopy using complex-amplitude correlation - Tamrin Khairul Fikri, Rahmatullah Bahbibi, Mohamad Samuri Suzani (N/A, 2014)
Astigmatism compensation in digital holographic microscopy using complex-amplitude correlation by Tamrin Khairul Fikri, Rahmatullah Bahbibi, Mohamad Samuri Suzani,